Restoring the Anteroposterior Shoulder Force Couple: Arthroscopic-Assisted Lower Trapezius Tendon Transfer With Partially Augmented Rotator Cuff Repair for Irreparable Massive Rotator Cuff Tears - Jianmin Zhang, M.D.; Guoyin Zhang, M.D.; Yang Yang, M.D.; Liwei Ying, M.D.; Li Ying, Ph.D.; Qingguo Zhang, M.D.; Xiaobo Zhou, M.D. (Arthroscopy Techniques)
Lower trapezius transfer presents a highly encouraging therapeutic approach for addressing posterosuperior irreparable massive rotator cuff tears. Based on studies on the balance of force couples of the rotator cuff, more scholars believe that attention should be paid to the reconstruction of the force couples of the rotator cuff. This study proposes a modified surgical approach that integrates an arthroscopic-assisted lower trapezius transfer with autologous hamstring tendon and partially augmented rotator cuff repair for irreparable massive rotator cuff tears, with a focus on restoring the anterior-posterior shoulder force couple.